2017
DOI: 10.1111/jpc.13735
|View full text |Cite
|
Sign up to set email alerts
|

Screening and referral for children with physical disabilities

Abstract: The clinical care of children with physical disabilities is a major priority for paediatricians and paediatric orthopaedic surgeons. Cerebral palsy (CP) is the prototypical condition and remains the most common cause of physical disability in developed countries. The incidence is approximately 2 per 1000 live births, translating to between 600 and 700 new children per annum in Australia, with approximately 34 000 children and adults currently living with CP. This figure is predicted to rise inexorably over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We also found that the necessary equipment for testing and diagnosis of CP was limited in most healthcare settings. HCPs reported that they often send CLWCPs to multiple locations to conduct diagnoses and access specialized treatments [37]. Due to the fragmentation of health services in Ghana, many families, especially those living in rural communities, struggle to access the required services promptly [15,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the necessary equipment for testing and diagnosis of CP was limited in most healthcare settings. HCPs reported that they often send CLWCPs to multiple locations to conduct diagnoses and access specialized treatments [37]. Due to the fragmentation of health services in Ghana, many families, especially those living in rural communities, struggle to access the required services promptly [15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers also rely on alternative medicine, such as herbs or spiritual healing, due to the desire for a permanent cure for CP, symptoms that were not sufficiently addressed by the medical system, perceptions about disability, cost, family referral, and poor provider relationship [36]. Despite the availability of a few services, studies show that finding providers who can offer the specific interventions that CLWCPs need can be challenging for caregivers in low-resource settings [37,38].…”
Section: The Ghanaian Healthcare System and Care For Children With Ce...mentioning
confidence: 99%